Five fictions in search of truth - Jehlen, Myra; IG Publishing (Princeton Princeton University Press, 2008)
Fiction, far from being the opposite of truth, is wholly bent on finding it out, and writing novels is a way to know the real world as objectively as possible. In Five Fictions in Search of Truth, Myra Jehlen develops this idea through readings of works by Flaubert, James, and Nabokov. She invokes Proust's famous search for lost memory as the exemplary literary process, which strives, whatever its materials, for a true knowledge. In Salammb, Flaubert digs up Carthage; in The Ambassadors, James plumbs the examined life and touches at its limits; while in Lolita, Nabokov traces a search for truth that becomes a trespass. In these readings, form and style emerge as fiction's means for taking hold of reality, which is to say that they are as epistemological as they are aesthetic, each one emerging by way of the other. The aesthetic aspects of a literary work are just so many instruments for exploring a subject, and the beauty and pleasure of a work confirm the validity of its account of the world. For Flaubert, famously, a beautiful sentence was proven true by its beauty. James and Nabokov wrote on the same assumption--that form and style were at once the origin and the confirmation of a work's truth.
A real madeleine is a work of art -- Salammbo : three rough stones beneath a rainy sky -- The sacred fount : the case of the man who became extraordinarily -- Amusing -- The ambassadors : what he saw was exactly the right thing -- Lolita : a beautiful, banal, eden-red apple -- A simple heart : Felicite and the holy parrot.
Electronic reproduction.
Keywords: Fiction -- 20th century -- History and criticism; Fiction -- 19th century -- History and criticism; Electronic books